Efficacy of Mouthwashes Containing Hydrogen Peroxide on Tooth Whitening - Muhammet Karadas; Omer Hatipoglu (The Scientific World Journal)
The aim of this study was to analyze the efficacy of mouthwashes containing hydrogen peroxide compared with 10% carbamide peroxide (CP) gel. Fifty enamel-dentin samples were obtained from bovine incisors and then stained in a tea solution. The stained samples were randomly divided into five groups according to the whitening product applied (n=10): AS: no whitening (negative control), with the samples stored in artificial saliva; CR: Crest 3D White mouthwash; LS: Listerine Whitening mouthwash; SC: Scope White mouthwash; and OP group: 10% CP Opalescence PF (positive control). Color measurements were carried out with a spectrophotometer before staining, after staining, and on the 7th, 28th, and 56th day of the whitening period. The data were analyzed using two-way analysis of variance followed by a Tukey post hoc test. The color change (ΔE) was significantly greater in all the groups compared to that of the AS group. After 56 days, no significant differences were found among the mouthwash products with respect to color change (P>0.05). The whiteness of the teeth treated with the mouthwashes increased significantly over time. Nevertheless, the color change achieved with the mouthwashes was significantly lower than that achieved with the 10% CP at-home bleaching gel.